Birds, Bees, and Botany: Measuring Urban Biodiversity After Nature-Based Solutions Implementation - Mónica Q. Pinto; Simone Varandas; Emmanuelle Cohen-Shacham; Edna Cabecinha (Diversity, 2025)
Nature-based Solutions (NbS) are increasingly adopted in urban settings to restore ecological functions and enhance biodiversity. This study evaluates the effects of NbS interventions on bird, insect, and plant communities in the Cavalum Valley urban green area, Penafiel (northern Portugal). Over a three-year period, systematic field surveys assessed changes in species richness, abundance, and ecological indicators following actions such as riparian restoration, afforestation, habitat diversification, and invasive species removal. Results revealed a marked increase in bird overall abundance from 538 to 941 individuals and in average pollinator population size from 9.25 to 12.20. Plant diversity also improved, with a rise in native and RELAPE-listed species (5.23%). Functional group analyses underscored the importance of vegetative structure in supporting varied foraging and nesting behaviours. These findings highlight the effectiveness of integrated NbS in enhancing biodiversity and ecological resilience in urban landscapes while reinforcing the need for long-term monitoring to guide adaptive management and conservation planning. Future work could evaluate ecological resilience thresholds and community participation in citizen science monitoring.